IPTEK PENCATATAN DAN PELAPORAN KEUANGAN UNIT USAHA BUMDes DI KABUPATEN KAMPAR - Neneng - Salmiah; Satria Tri Nanda, Intan Adino (KUAT : Keuangan Umum dan Akuntansi Terapan, 2020)
This community service program aims to increase the knowledge and capabilities of BUMDes Business Unit Managers in Kampar Regency, especially in Kampar Kiri Tengah District in making financial records and reporting so that they can be used to assess business performance and as a BUMDes responsibility for annual village accountability meetings. The method used in this activity is counseling and training methods by providing knowledge about the recording and financial reporting of BUMDes Business Units according to the type of business unit. The activity was continued by providing a simulation of recording and compiling financial reports in accordance with the BUMDes business unit. To measure the success rate of the activities carried out, pre and post tests will be carried out. In this training activity, the manager of the Kampar Regency BUMDes Business Unit will be involved collaboratively from the beginning to the end of the activity. Output targets are to increase knowledge and financial recording and reporting capabilities and scientific articles that will be published at the national level. The results of this community service can be seen from the answers pre and post test relating to the type of business, accounting cycle, type of financial statements, financial accounting standards and recording with special journals where there is a decrease in the answers of most of the participants answering not knowing and after being given counseling and technical guidance, the answers do not know on average to be 0%. This shows that there is an increase in knowledge of recording and financial reporting for the managers of BUMDes business units.